An exploratory study of dairying intensification, women’s decision making, and time use and implications for child nutrition in Kenya - Njuki, Jemimah; Wyatt, Amanda; Baltenweck, Isabelle; Yount, K.; Null, C.; Ramakrishnan, U.; Girard, Amy W.; Sreenath, S. (Springer, 2016)
Dairy intensification as a development strategy is expected to improve household nutrition, yet the pathways by which this occurs are not well understood. This article examines how women’s time use and decision-making patterns related to dairy income and consumption are associated with dairy intensification, as a way of exploring the links between intensification and nutrition. Results from our mixed methods study conducted with households representing low, medium and high levels of dairy intensification in rural Kenya indicated that children in high-intensity households received more milk than children in medium-intensity households. While women seemed to be gaining control over evening milk sales decisions, men seemed to be increasingly controlling total dairy income, a trend countered by the increase in reported joint decision making. Women from medium-intensity households reported spending more time on dairy activities than women from high-intensity households. More research on how dairy interventions affect women is needed.